An Error Analysis Of Students’ Pronunciation On Tongue Twister Game At 7th Grade Students Of Mts Yusufiyah - Fifi Rahayu; Yanti Rusmiati (Nusantara Journal of Multidisciplinary Science, 2023)
This research goal to find out An Error Analysis of Students’ Pronunciation on Tongue Twister Game at 7th grade Students of Mts Yusufiyah Jakarta in academic year 2022/2023. And this research used qualitative method because it’s classroom Action research. Researcher found some problems when the students pronounce tongue twister game words such as I scream, you scream, we all scream for ice cream; Fuzzy Wuzzy was a bear, Fuzzy Wuzzy had no hair, Fuzzy Wuzzy wasn’t fuzzy, was he; She sells seashells by the seashore, The shells she sells are seashells I’m sure, for if she sells seashells by the seashore. Then I’m sure she sells seashore shells. Data was collected through questionnaire with sixteen students at grade Students of Mts Yusufiyah Jakarta. To explain the data the researcher used descriptive qualitative method. The result showed that three cycles different errors. In the first cycle :58.98%, in the second cycle: 26,72% and the last cycle: 14,28%. This’s good result the students’ error in every cycle reduce